Influenza Knowledge, Attitude, and Behavior Survey for Grade School Students: Design and Novel Assessment Methodology - Koep, Tyler H. (J Community Health, 2014)
BACKGROUND: Despite the fact infectious diseases can spread readily in grade schools, few studies have explored prevention in this setting. Additionally, we lack valid tools for students to self-report knowledge, attitudes, and behaviors. As part of an ongoing study of a curriculum intervention to promote healthy behaviors, we developed and evaluated age-appropriate surveys to determine students’ understanding of influenza prevention. METHODS: Surveys were adapted from adolescent and adult influenza surveys and administered to students in grades 2–5 (ages 7–11) at two Rochester public schools. We assessed student understanding by analyzing percent repeatability of 20 survey questions and compared percent “Don’t Know” (DK) responses across grades, gender, and race. Questions thought to be ambiguous after early survey administration were investigated in student focus groups, modified as appropriate, and reassessed. RESULTS: The response rate across all surveys was > 87%. Survey questions were well understood; 17 of 20 questions demonstrated strong pre/post repeatability (> 70%). Only 1 question showed an increase in DK response for higher grades (p <.0001). Statistical analysis and qualitative feedback led to modification of 3 survey questions and improved measures of understanding in the final survey administration. CONCLUSIONS: Grade-school students’ knowledge, attitudes and behavior toward influenza prevention can be assessed using surveys. Quantitative and qualitative analysis may be used to assess participant understanding and refine survey development for pediatric survey instruments. These methods may be used to assess the repeatability and validity of surveys to assess the impact of health education interventions in young children.